Chinese looks : fashion, performance, race - Metzger, Sean, 1973- (Bloomington, IN : Indiana University Press, 2014)
From yellow-face performance in the 19th century to Jackie Chan in the 21st, Chinese Looks examines articles of clothing and modes of adornment as a window on how American views of China have changed in the past 150 years. Sean Metzger provides a cultural history of three iconic objects in theatrical and cinematic performance: the queue, or man''s hair braid; the woman''s suit known as the qipao; and the Mao suit. Each object emerges at a pivotal moment in US-China relations, indexing shifts in the balance of power between the two nations. Metzger shows how aesthetics, gender, politics, econom.
Cover; Contents; Acknowledgments; Introduction; PART 1 THE QUEUE; 1 Charles Parsloe's Chinese Fetish; 2 Screening Tails; PART 2 THE QIPAO; 3 Anna May Wong and the Qipao's American Debut; 4 Exoticus Eroticus, or the Silhouette of Suzie's Slits during the Cold War; 5 Cut from Memory: Wong Kar-Wai's Fashionable Homage; PART 3 THE MAO SUIT; 6 An Unsightly Vision; 7 Uniform Beliefs?; 8 Mao Fun Suits; Epilogue; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z.
Print version record.
Includes bibliographical references and index.
English.
JSTOR
Keywords: Fashion -- China; Fashion design -- China; Popular culture -- China; Chinese in motion pictures; Culture populaire -- Chine; Chinois au cinéma.; DESIGN -- Textile & Costume; PERFORMING ARTS -- Film & Video -- History & Criticism; Chinese in motion pictures; Fashion; Fashion design; Manners and customs; Popular culture; Race relations; China; Mode; Modedesign; Folkkultur